Beneficial effects of Bacillus mojavensis strain MTC-8 on plant growth, immunity and disease resistance against Magnaporthe oryzae - Ze, Mu; Ma, Feimin; Zhang, Jihong; Duan, Jichao; Feng, Dingjin; Shen, Yaoru; Chen, Guanwei; Hu, Xiaohong; Dong, Ming; Qi, Tuo; Zou, Lijuan (Frontiers in Microbiology, 2024)
Rice blast, a prevalent and highly destructive rice disease that significantly impacts rice yield, is caused by the rice blast fungus. In the present study, a strain named MTC-8, identified as Bacillus mojavensis, was demonstrated has strong antagonistic activity against the rice blast fungus, Rhizoctonia solani, Ustilaginoidea virens and Bipolaria maydis. The potential biocontrol agents were identified using ultra-performance liquid chromatography -tandem mass spectrometry (UPLC-MS/MS) analysis and chromatography. Further investigations elucidated the inhibitory mechanism of the isolated compound and demonstrated its ability to suppress spore germination, alter hyphal morphology, disrupt cell membrane integrity, and induce defense-related gene expression in rice. MTC-8 promoted plant growth and may lead to the development of a biocontrol agent that meets agricultural standards. Overall, the Bacillus mojavensis MTC-8 strain exerted beneficial effects on plant growth, immunity and disease resistance against rice blast fungus. In this study, we isolated and purified a bioactive substance from fermentation broth, and the results provide a foundation for the development and application of biopesticides.Elucidation of the inhibitory mechanism against rice blast fungus provides theoretical support for the identification of molecular targets. The successful development of a biocontrol agent lays the groundwork for its practical application in agriculture.